A Study on internet addiction among teenagers in selangor state of malaysia - Raja Kumar Murugesan; Binti Mohd Hamzaht Siti Khadijah; Supriyanto (MATEC Web of Conferences, 2018)
Internet addiction is becoming a growing phenomenon across the world due to the tendency of Internet overuse for varied reasons. The objective of this study is to identify the extent of Internet use and level of addiction among teenagers with the age ranging from 13 to 17 years old. This also include the risk factor and impact to their social life. The sample data were taken from several schools covering 500 students from the state of Selangor in Malaysia. The survey was done using an instrument from Internet Addiction Test (IAT) developed by Dr. Kimberly Young. This test had been modified to meet the requirements of the youngster’s mind-set in Malaysia. Demographics factors such as age, gender and race were examined apart from family and personal factors. The results of the study and Chi-square test summarizes that the level of internet addiction among teenagers in Selangor is p = 0.161 and tends to be minimal. We need to be aware of the level of Internet usage by teenagers so that measures could be made in place to deter or mitigate Internet addiction.